2016
DOI: 10.1111/tmi.12800
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic test for G6PD deficiency in Plasmodium vivax‐infected men: a budget impact analysis based in Brazilian Amazon

Abstract: Abstractobjective The aim of this study was to estimate the incremental budget impact (IBI) of a rapid diagnostic test to detect G6PDd in male patients infected with Plasmodium vivax in the Brazilian Amazon, as compared with the routine protocol recommended in Brazil which does not include G6PDd testing.methods The budget impact analysis was performed from the perspective of the Brazilian health system, in the Brazilian Amazon for the years 2013, 2014 and 2015. The analysis used a decision model to compare two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Previous CEAs have already demonstrated that strategies based on the use of the qualitative rapid diagnostic test (CareStart G6PD) were cost-effective [ 19 , 32 ], including in the Brazilian Amazon. Other studies have indicated that the strategy based on CareStart G6PD were cost-effective in avoiding hospitalization and showed a negative incremental budget impact [ 33 ]. Our study demonstrates that quantitative testing with SD biosensor remains cost-effective while including technological advantages, such as the important gains in diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous CEAs have already demonstrated that strategies based on the use of the qualitative rapid diagnostic test (CareStart G6PD) were cost-effective [ 19 , 32 ], including in the Brazilian Amazon. Other studies have indicated that the strategy based on CareStart G6PD were cost-effective in avoiding hospitalization and showed a negative incremental budget impact [ 33 ]. Our study demonstrates that quantitative testing with SD biosensor remains cost-effective while including technological advantages, such as the important gains in diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In places in which movements are not easily restricted–such as urban centres in which dog populations are contiguous–our study indicates that comprehensive vaccination coverage is crucial and that reducing population turnover (for example, by increasing veterinary care to improve dog health) might not have a substantial effect on reducing the vaccination coverage required. The political and operational challenges of rabies elimination are well-documented [50], and lack of elimination or subsequent re-emergence is attributed to insufficient vaccination coverage (< 70% dog population overall, patchy coverage or insufficient duration [49, 51, 52]) and re-introduction of infected dogs [48, 53]. Pockets of unvaccinated dogs within well-vaccinated, urban areas could maintain rabies at a low incidence sufficient to re-introduce rabies as surrounding herd immunity wanes.…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, it will enable the safe treatment of more patients with deficient and intermediate G6PD activity, diminishing the risk of recurrent malaria and acute hemolytic anemia (5,7,31,32). At the healthcare systems level, it could reduce the associated costs and the burden on transfusion services by reducing the number of hemolytic crises caused by PQ or TQ in individuals with unknown G6PD status and malaria treatment (5,7,31,33). Additionally, this could impact parasite transmission rates when combined with other interventions (5,7,31).…”
Section: Discussionmentioning
confidence: 99%